The Small-size Ionic-plasma Engine for Nanosatellites. (2017) - Phylonin, Oleg; Belokonov, Igor
Abstract: The miniature ion-plasmatic engine for Cube Sate nanosatellites is described. The working body is the mercury ions received from metal mercury by radiation from its cesium source. The offered construction allows NS trajectory parameters to be changed, to compensate oscillating and rotational motions of the device. Examples of calculation of the IPE some parameters are given.